Emergence of Neisseria meningitidis W-135 in the context of other rare serogroups. (February 2012) - da Silva, Luiz Jacintho; DeTora, Lisa; Malerczyk, Claudius; Memish, Ziad A
Neisseria meningitidis can be considered a continually emerging pathogen due to its genetic mutability and dynamic epidemiology. Currently, six serogroups (A, B, C, W-135, X and Y) are important to global disease epidemiology. Until 2000, serogroup W-135 was rare worldwide. Hajj-associated W-135 outbreaks caused by a virulent ST-11 strain in 2000 and 2001 raised concerns about widespread epidemic disease. Serogroup W-135 now circulates worldwide. Serogroup X recently gained health authority attention because of dramatic attack and case fatality rates during recent outbreaks in Africa. Serogroups Z and 29E, in contrast, have remained rare. Some genetic and other mechanisms behind serogroup epidemiology remain poorly understood. Additional surveillance and typing information is necessary to assist these efforts and to inform vaccine policy.